National Health Interview Survey, 1996 ([Verlag nicht ermittelbar], 1999)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The variables in the Household Record file (Part 1) include type of living quarters, size of family, number of families in the household, presence of a telephone, number of unrelated individuals, and region. The Person Record file (Part 2) includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, employment status, and industry and occupation. These variables are found in the Condition, Doctor Visit, and Hospital Record files as well. The Person Record also supplies data on height, weight, bed days, doctor visits, hospital stays, years at residence, and region variables. The Condition Record file (Part 3) contains information for each reported health condition, with specifics on injury and accident reports. The Doctor Visit Record file (Part 4) documents doctor visits within the time period and identifies acute or chronic conditions. The Hospital Record file (Part 5) provides information on medical conditions, hospital episodes, type of service, type of hospital ownership, date of admission and discharge, number of nights in hospital, and operations performed.